2019
DOI: 10.26877/jipmat.v4i1.3663
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Pembelajaran Entrepreneur Berbasis Matematika

Abstract: Di Indonesia masih banyak pengangguran dan makin kecil peluang untuk mendapatkan pekerjaan bagi para lulusan sekolah. Diperlukan inovasi pengajar dalam pembelajaran untuk menumbuhkan karakter siswa seperti kerja keras, tanggung jawab, ulet, jujur, dan sebagainya, dalam karakter tersebut bisa dirangkum sebagai karakter kewirausahaan. Karakter kewirausahaan perlu ditumbuhkan pada setiap siswa untuk membentuk jiwa wirausaha, sehingga dapat mewujudkan pembangunan ekonomi dan membuka lapangan kerja sendiri. Untuk m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Based on the results of the entrepreneurship-based mathematics E-Module validation test by 3 validators presented in table 2, it can be concluded that the entrepreneurship-based mathematics E-Module developed is valid with an average score percentage of the three validators of 92,88% and included in the category "Very Eligible ". The entrepreneurship-based mathematics e-module which has been declared valid contains the basic skills of entrepreneurship according to Ronald J.Ebert (Masduki & Kurniasih, 2019) namely (1) technical skills (skills in carrying out tasks), where in the entrepreneurship-based mathematics E-Module students are given assignments both individually and in groups containing contextual problems related to entrepreneurship so that students have an obligation to complete them, (2) human relations skills (skills to understand, understand and communicate with other people), where in the entrepreneurship-based math E-Module students are trained to collaborate with their classmates in completing assignments given in the E-Module, (3) conceptual skills (abstract thinking skills in facing challenges), where through the problems presented in this E-Module in the form of non-routine problems so that students are trained to be able to think more deeply in solving these problems, (4) decision making skills, (skills for formulating problems) with the tasks in the E-Module given to students, students are trained to be able to decide on a problem solving strategy that must be done to complete the task; (5) time management skills (skills to use time as productively as possible), with the problems given in this E-Module students and their groups are trained so that they can make the best use of time to solve the given problems.…”
Section: Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of the entrepreneurship-based mathematics E-Module validation test by 3 validators presented in table 2, it can be concluded that the entrepreneurship-based mathematics E-Module developed is valid with an average score percentage of the three validators of 92,88% and included in the category "Very Eligible ". The entrepreneurship-based mathematics e-module which has been declared valid contains the basic skills of entrepreneurship according to Ronald J.Ebert (Masduki & Kurniasih, 2019) namely (1) technical skills (skills in carrying out tasks), where in the entrepreneurship-based mathematics E-Module students are given assignments both individually and in groups containing contextual problems related to entrepreneurship so that students have an obligation to complete them, (2) human relations skills (skills to understand, understand and communicate with other people), where in the entrepreneurship-based math E-Module students are trained to collaborate with their classmates in completing assignments given in the E-Module, (3) conceptual skills (abstract thinking skills in facing challenges), where through the problems presented in this E-Module in the form of non-routine problems so that students are trained to be able to think more deeply in solving these problems, (4) decision making skills, (skills for formulating problems) with the tasks in the E-Module given to students, students are trained to be able to decide on a problem solving strategy that must be done to complete the task; (5) time management skills (skills to use time as productively as possible), with the problems given in this E-Module students and their groups are trained so that they can make the best use of time to solve the given problems.…”
Section: Developmentmentioning
confidence: 99%
“…(5) time management skills (Masduki & Kurniasih, 2019). This research will produce valid, practical and effective E-Modules and learning tools in the form of a syllabus and Learning Implementation Plan to improve students' mathematical problem solving abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Contextual learning in the surrounding environment can increase student activities, scientific literacy learning outcomes, process skills, and scientific attitudes (Dwianto et al, 2017;Setiawan et al, 2017;Sunarsih et al, 2020). The diversity of local potential-based learning resources is effective in the learning process (Masduki & Kurniasih, 2019).…”
Section: Highmentioning
confidence: 99%
“…Hasil tersebut menunjukan bahwa bahan ajar yang didesain dengan baik mampu mengoptimalkan kemampuan literasi matematis dan jiwa kewirausahaan (Ashoer et al, 2004;Supriatna, 2017). Salah hal yang menarik karena bahan ajar yang di desain demikian dapat membantu siswa mengembangkan kemampuan berpikir kreatif sebagai dasar dalam pemecahan masalah sehari-hari, dan kemampuan berpikir kreatif juga sebagai dasar dalam membangun jiwa kewirausahaan yang baik (Hadiyati, 2011;Masduki & Kurniasih, 2019). Perlu sekiranya pengembangan bahan ajar selanjutnya pada materi diluar aritmetika sehingga siswa mampu mengoptimalkan kemampuan literasi matematis dan jiwa kewirausahannya.…”
Section: Gambar 1 Tim Pelaksanaan Pengabdianunclassified